PENGARUH MODEL TALKING STICK TONGKAT BUBBLE TERHADAP PEMAHAMAN DAN KEMANDIRIAN BELAJAR PADA MATEMATIKA SD MUHAMMADIYAH - Zeinab, Siti; Arifin, Zainal; Kusuma, Rendra Sakbana; Yuliati, Ana (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This study intends to be abble to see the difference in the effect of Talking Stick and Conventionallearning models on students’ understanding and learning on understanding and learning independence in mathematics class I SD Muhammadiyah 1 Bangkalan with this quanntitative appoach using Quasi Experimental Design. The sample used was grade 1A and B students of SD Muhammadiyah 1 Bangkalan, totaling 43 students in total. Instruments used in the form of student learning comprehension questions and independence questionnaires. While the analysistest is validity test, reliability test, homogeneity test, normality test and independent sample t-test with the help of SPSS application. This is evidenced in the use of learning models in mathematics lessons to improve student’s understanding and learning independence obtained a significant value (2-tailed) of 0.000 < 0,05 which states that there are differences in the understanding and learning independence of student who use the talking stick and conventional learning models.